Measures of atherosclerotic burden are associated with clinically manifest cardiovascular disease in type 2 diabetes: a European cross‐sectional study. (13th April 2015) - Shore, A. C.; Colhoun, H. M.; Natali, A.; Palombo, C.; Östling, G.; Aizawa, K.; Kennbäck, C.; Casanova, F.; Persson, M.; Gooding, K.; Gates, P. E.; Khan, F.; et al.
Abstract Background There is a need to develop and validate surrogate markers of cardiovascular disease (CVD) in subjects with diabetes. The macrovascular changes associated with diabetes include aggravated atherosclerosis, increased arterial stiffness and endothelial dysfunction. The aim of this study was to determine which of these factors is most strongly associated with clinically manifest cardiovascular events. Methods Vascular changes were measured in a cohort of 458 subjects with type 2 diabetes (T2D) and CVD (myocardial infarction, stroke or lower extremity arterial disease), 527 subjects with T2D but without clinically manifest CVD and 515 subjects without T2D and with or without CVD. Results Carotid intima–media thickness (IMT) and ankle–brachial pressure index were independently associated with the presence of CVD in subjects with T2D, whereas pulse wave velocity and endothelial function provided limited independent additive information. Measurement of IMT in the carotid bulb provided better discrimination of the presence of CVD in subjects with T2D than measurement of IMT in the common carotid artery. The factors most significantly associated with increased carotid IMT in T2D were age, disease duration, systolic blood pressure, impaired renal function and increased arterial stiffness, whereas there were no or weak independent associations with metabolic factors and endothelial dysfunction. Conclusions Measures of atherosclerotic burden are associated with clinically manifest CVD in subjects with T2D. In addition, vascular changes that are not directly related to known metabolic risk factors are important in the development of both atherosclerosis and CVD in T2D. A better understanding of the mechanisms involved is crucial for enabling better identification of CVD risk in T2D.